Medication Assisted Treatment in the Treatment of Drug Abuse and Dependence in HIV/AIDS Infected Drug Users - Kresina, Thomas F.; Bruce, R. D.; McCance-Katz, Elinore F. (Current HIV Research, 2009)
Drug use and HIV/AIDS are global public health issues. The World Health Organization (WHO) estimates that up to 30% of HIV infections are related to drug use and associated behaviors. The intersection, of the twin epidemics of HIV and drug/alcohol use, results in difficult medical management issues for the health care providers and researchers who work in the expanding global HIV prevention and treatment fields. Access to care and treatment, medication adherence to multiple therapeutic regimens, and concomitant drug -drug interactions of prescribed treatments are difficult barriers for drug users to overcome without directed interventions. Injection drug users are frequently disenfranchised from medical care and suffer sigma and discrimination creating additional barriers to care and treatment for their drug abuse and dependence as well as HIV infection. In an increasing number of studies, medication assisted treatment of drug abuse and dependence has been shown to be an important HIV prevention intervention. Controlling the global transmission of HIV will require further investment in evidence-based interventions and programs to enhance access to care and treatment of individuals who abuse illicit drugs and alcohol. In this review, we present the cumulative evidence of the importance of medication assisted treatment in the prevention, care, and treatment of HIV infected individuals who also abuse drugs and alcohol.
Keywords: HIV/AIDS